Meat Grade and Preservation Enhancement through Natural Substance Marinades: An Evaluation - Nithya MS, Naresh Kore, Vikram singh (Revista Electronica de Veterinaria, 2024)
Traditional methods of enhancing meat quality, such as marinating it have been altered as a consequence of people’s desire to label goods. Meat marination is a culinary method that allows meat to be soaked or coated in a tasty concoction to improve its texture, flavor, and juiciness.The process of using several methods to keep meat products fresher longer and prevent them from spoiling or decomposing is referred as meat preservation.To focus on the effects of using marinades made of natural substances on the quality and preservation of meat.The analysis demonstrated that natural marinades increase the meats sensory appeal, enhance its culinary qualities, and lengthen its shelf life. Inhibit the metabolism of proteins and lipids, which has an impact on the healthiness of meat products. Also lessens the production of polycyclic aromatic hydrocarbons (PAHs) and heterocyclic aromatic amines (HAAs), as well as biogenic amines.An extensive analysis was carried out on articles using the natural ingredients in meat marinades that were covered in the years 2019 to 2023. In particular, it focused on the examination of a range of substances, such as wine and beer, as well as fruits, vegetables, spices, and fermented dairy products.It was shown that using natural marinades improves both the meat’s flavor and texture while extending its preservation life. These marinates improve meat quality by avoiding lipid and protein oxidation.The competing microbiota from dairy products and physiologically active ingredients make this feasible. Nevertheless, some marinades, particularly those with acidic contents, result in an unfavorable color shift and a mildly acidic flavor. Research on the influence of organic marinates on nutrients and Promotes wellness properties of meat based goods are significantly absent.The findings demonstrated a substantial favorable relationship between the usage of natural ingredient marinades and overall meat grade improvement.